From Coexistence to Cooperation: Religious Moderation, Civil Pluralism, and Interfaith Social Capital in Kampung Pondok - Eliza; Duski Samad; Erwin; Khairul Fahmi; Rahmad Tri Hadi (Islam Realitas: Journal of Islamic and Social Studies, 2026)
Religious moderation is increasingly promoted as a framework for managing religious diversity in Indonesia, yet its everyday grassroots practices remain underexplored. This study examines how religious moderation is constructed and sustained among Muslim, Christian, Buddhist, and Confucian communities in Kampung Pondok, Padang. Using a qualitative case study, data were collected through in-depth interviews, participant observation, and document analysis. The findings show that religious moderation operates through two interconnected dimensions: preventive and constructive. The preventive dimension is reflected in inclusive social norms, mutual restraint, and informal mechanisms that reduce potential religious tensions. The constructive dimension emerges through interfaith dialogue, reciprocal assistance, collective responsibility, and sustained cultural interaction. These practices are reinforced by Minangkabau local wisdom, which strengthens civic pluralism, interpersonal trust, and interfaith social capital. The study argues that religious moderation functions not only as a mechanism for preventing conflict but also as a productive social process that transforms passive coexistence into active interfaith cooperation. This grassroots perspective offers insights into resilient religious pluralism in Indonesia and other diverse Southeast Asian societies.